Exploring Indigenous Materials for Creative Drawing as an Alternative Resource for Sustainable Development in Least Developed Countries - Odongo , Michael (African Journal of Education,Science and Technology (AJEST), 2018)
The fourth Sustainable Development Goal of quality education for all is one of the most powerful and proven vehicles for sustainable development. To achieve this goal through Art and Design Education, there is need for innovation and improvisation of materials to encourage and motivate learners who can’t afford the compulsory manufactured materials required for drawing. Much as there are plenty of indigenous materials to provide stain/pigment for drawing very few artists and facilitators have taken time to explore and experiment on different alternatives for creative drawing. In a bid to discover the potential of indigenous materials for drawing, the survey was conducted on different plants and rock substances, through different processes of extraction like grinding, smashing, blending among others, different colour stains such as green, yellow, red, blue and purple was extracted from these inorganic and organic materials. The findings found out there are plenty materials readily available around our surroundings from which colour pigments can be extracted and used for creative drawing. The study is expected to promote the use of indigenous natural materials for quality Drawing and make learning and teaching art economically viable across all levels of education.